The rejuvenating influence of young plasma on aged intestine - Ceylani, Taha; Teker, H.T.; Keskin, S.; Samgane, G.; Acikgoz, E.; Gurbanov, R. (John Wiley and Sons Inc, 2023)
This study aims to investigate the effects of plasma exchange on the biomolecular profiles and histology of ileum and colon tissues in young and aged Sprague–Dawley male rats. Fourier transform infrared (FTIR) spectroscopy, linear discriminant analysis and support vector machine (SVM) techniques were employed to analyse the lipid, protein, and nucleic acid indices in young and aged rats. Following the application of young plasma, aged rats demonstrated biomolecular profiles similar to those of their younger counterparts. Histopathological and immunohistochemical assessments showed that young plasma had a protective effect on the intestinal tissues of aged rats, increasing cell density and reducing inflammation. Additionally, the expression levels of key inflammatory mediators tumour necrosis factor-alpha and cyclooxygenase-2 significantly decreased after young plasma administration. These findings underscore the therapeutic potential of young plasma for mitigating age-related changes and inflammation in the intestinal tract. They highlight the critical role of plasma composition in the ageing process and suggest the need for further research to explore how different regions of the intestines respond to plasma exchange. Such understanding could facilitate the development of innovative therapies targeting the gastrointestinal system, enhancing overall health during ageing. © 2023 The Authors. Journal of Cellular and Molecular Medicine published by Foundation for Cellular and Molecular Medicine and John Wiley & Sons Ltd.
Keywords: Aging; Cell Density; Inflammation; Intestinal Tissue; Ir Spectroscopy; Machine Learning; Plasma Exchange; Sprague-Dawley Rat; Cyclooxygenase 2; Tumor Necrosis Factor; Aged; Aging; Animal Experiment; Animal Tissue; Antiinflammatory Activity; Article; Cell Density; Colon Tissue; Discriminant Analysis; Fourier Transform Infrared Spectroscopy; Gastrointestinal Tract; Gene Expression; Histology; Histopathology; Ileum Tissue; Immunohistochemistry; Inflammation; Intestine; Lipid Composition; Machine Learning; Male; Nonhuman; Plasma; Plasma Exchange; Protein Carbonylation; Protein Expression; Protein Phosphorylation; Rat; Rejuvenation; Support Vector Machine; Animal; Sprague Dawley Rat; Animals; Gastrointestinal Tract; Inflammation; Intestines; Male; Plasma; Rats; Rats, Sprague-Dawley